Complete mitochondrial genome and taxonomic revision of Cardiodactylus muiri Otte, 2007 (Gryllidae: Eneopterinae: Lebinthini) - Dong, Jiajia; Vicente, Natallia; Chintauan-Marquier, Ioana C.; Ramadi, Cahyo; Dettai, Agnès; Robillard, Tony (Zootaxa, 2017)
In the present study, we report the high-coverage complete mitochondrial genome (mitogenome) of the cricket Cardiodactylus muiri Otte, 2007. The mitogenome was sequenced using a long-PCR approach on an Ion Torrent Personal Genome Machine (PGM) for next generation sequencing technology. The total length of the amplified mitogenome is 16,328 bp, representing 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one noncoding region (D-loop region). The new sets of long-PCR primers reported here are invaluable resources for future comparative evolutionary genomic studies in Orthopteran insects. The new mitogenome sequence is compared with published cricket mitogenomes. In the taxonomic part, we present new records for the species and describe life-history traits, habitat and male calling song of the species; based on observation of new material, the species Cardiodactylus buru Gorochov & Robillard, 2014 is synonymized under C. muiri.